Potensi Bioremediasi Mikroplastik Menggunakan Bakteri di Pengelolaan Air Limbah: The Potential of Microplastic Bioremediation Using Bacteria in Wastewater Treatment Systems - Mahesa Dhiyaa Alkhairan; Siti Nurbaeti; Alifah Mustari Mukti Wibawa (Jurnal Biodiversitas dan Bioteknologi, 2025)
The issue of microplastic pollution is increasing due to the widespread use of plastics in daily life. Microplastics, which are less than 5 millimeters in size, are divided into two types: primary and secondary microplastics. Their presence in wastewater is one of the sources of pollution that can harm aquatic ecosystems and humans. Conventional wastewater treatment has limitations in effectively removing microplastics, thus requiring more efficient and environmentally friendly alternative approaches. One promising solution is bioremediation using bacteria, where certain bacteria can degrade microplastics into simpler compounds. Some types of bacteria effective in microplastic degradation include Pseudomonas aeruginosa, Bacillus subtilis, and Streptomyces thermoviolaceus. This study aims to explore the potential of bacteria in microplastic remediation in wastewater treatment plants (WWTPs). Research shows that bacteria can degrade microplastics with varying efficiency, depending on the type of bacteria and microplastics used. Integrating bioremediation with conventional wastewater treatment systems, such as activated sludge reactors, can improve the effectiveness of microplastic removal. However, further research is needed to ensure successful implementation on a larger scale. Considering ecological and economic aspects, microplastic bioremediation could become a long-term solution for reducing plastic pollution.